1990
DOI: 10.1067/mva.1990.18087
|View full text |Cite
|
Sign up to set email alerts
|

The management of vascular injuries associated with total hip arthroplasty

Abstract: Approximately 100,000 total hip reconstructions are done annually in the United States. The nature of the surgical technique in a field close to the iliac and femoral vessels makes the occurrence of vascular injury an occasional but serious complications. We have reviewed retrospectively our experience of five cases of vascular injuries with total hip replacement and an additional 63 cases in the literature to identify those patients at risk and to define the management of these injuries. For the entire group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…10 Hip arthroplasties and cement-related and retractor injuries have been reported as the main mechanisms of iliac lesions. 11,12 In our series, two patients sustained iliac vein injuries during an arthroplasty and two sustained iliac artery and vein injuries caused by the insertion of screws during arthrodesis. The injuries associated with limb ischemia were diagnosed and treated late, with high associated morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…10 Hip arthroplasties and cement-related and retractor injuries have been reported as the main mechanisms of iliac lesions. 11,12 In our series, two patients sustained iliac vein injuries during an arthroplasty and two sustained iliac artery and vein injuries caused by the insertion of screws during arthrodesis. The injuries associated with limb ischemia were diagnosed and treated late, with high associated morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have found subclinical electromyography-derived evidence of SGN injury [6,[19][20][21]. Female gender is the most well-established risk factor for neurologic injury during THA, with multiple studies reporting that at least 74% of these events occur in women [4,18,22,23].The external iliac artery and femoral artery are the most frequently injured vascular structures in THA [9]. Acetabular retractors placed too far medially are the most frequent cause of femoral artery injury [7,24,25].…”
mentioning
confidence: 98%
“…Vascular injury in THA, with a reported incidence of 0.1% to 0.2%, is less common than neurologic injury but more emergent [7]. False aneurysm or fistula formation, thromboembolism, loss of limb, or even mortality may result [8][9][10][11][12].In THA, the most common identifiable cause of intraoperative nerve injury is compression by retractors [13]. In order of decreasing frequency, the sciatic, femoral, and superior gluteal nerves (SGN) are most commonly injured during THA [3,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen of the 26 cases occurred during revision surgery and 86% occurred either immediately or within 48 hours of surgery. Shoenfeld et al [10] retrospectively reviewed five patients from their experience and 63 from the literature to further define vascular injury during hip arthroplasty. Thirty-nine percent of these injuries occurred in revisions and 43% required emergent surgery.…”
Section: Discussionmentioning
confidence: 99%